Learning engineering practice - Trevelyan, James P. (Leiden, The Netherlands : CRC Press/Blakema, 2021)
"This book explains engineering practice, what engineers actually do in their work. The first part explains how to find paid engineering work and prepare for an engineering career. The second part explains the fundamentals of engineering practice, including how to gain access to technical knowledge, how to gain the willing collaboration of other people to make things happen, and how to work safely in hazardous environments. Other chapters explain engineering aspects of project management missed in most courses, how to create commercial value from engineering work and estimate costs, and how to navigate cultural complexities successfully. Later chapters provide guidance on sustainability, time management and avoiding the most common frustrations encountered by engineers at work. This book has been written for engineering students, graduates and novice engineers. Supervisors, mentors and human resources professionals will also find the book helpful to guide early-career engineers and assess their progress. Engineering schools will find the book helpful to help students prepare for professional internships and also for creating authentic practice and assessment exercises"--
OCLC-licensed vendor bibliographic record.
Keywords: Engineering -- Practice; Engineering -- Vocational guidance; TECHNOLOGY / Engineering / General; TECHNOLOGY / Engineering / Civil; TECHNOLOGY / Engineering / Industrial